AN ANALYSIS OF DEIXIS TYPES AND ITS’ REFERENCE IN “CINDERELLA” MOVIE - Kadek Ari Widianti; Ni Luh Nyoman Seri Malini; Nissa Puspitaning Adni (ELTIN Journal, 2024)
The study aims to identify deixis types and their references in "Cinderella." Kenneth Branagh directed and Chris Weitz screen played this film. This study used descriptive qualitative research. The info came from the Cinderella script. The data was evaluated using Levinson's theory. The research discovered five types of deixis in Cinderella: person (998), spatial (84), time (47), place (98), and discourse (66). Furthermore, the reference meaning conveyed in deictic markers within the deixis found in the movie are revealed using the theory of anaphora such as anaphoric and cataphoric references.